MEDIATING EFFECTS OF ORGANIZATIONAL SUPPORT ON RELATIONSHIP BETWEEN ADMINISTRATORS' SERVANT LEADERSHIP AND TEACHERS' COMPETENCIES IN HIGHER VOCATIONAL COLLEGES IN JINAN, SHANDONG PROVINCE - FANG, XIE; muangman, pornthep; Tipanark, Peerapong (วารสารนิสิตวัง, 2026)
The objectives of this research were: (1) To examine the components of administrators' servant leadership, teachers' competencies and organizational support.; (2) To develop the model of mediating effects of organizational support on relationship between administrators' servant leadership, and teachers' competencies in higher vocational colleges in Jinan, Shandong province. (3) To study direct and indirect effects of administrators' servant leadership on teachers' competencies through mediating effects of organizational support. This research adopts a quantitative research approach. The research population consists of 7,563 in-service teachers from 15 higher vocational colleges in Jinan, Shandong Province. The required sample size was decided using G*Power program, and a total of 368 teachers were selected as the sample through proportional stratified random sampling. A semi-structured questionnaire was employed as the measurement instrument. Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) were conducted to examine the reliability and validity of the measurement model and to assess the overall fit of the hypothesized structural model. The results indicated that: 1) Administrators' servant leadership had 5 components: (1) Emotional Healing, (2) Empowerment, (3) Modeling, (4) Putting Others First, (5) Trust. Teachers' competencies had 5 components: (1) Instructional Design and Implementation Competency,(2)Educational Research and Reflective Competency, (3) Professional Development and Lifelong Learning Competency, (4) Digital Technology and Innovation Competency, (5) Communication and Collaboration Competency, and Organizational support had 3 components: (1) Work Support,(2) Emotional Support, (3) Respect/Recognition Support; 2) after modifying the measurement model, the model fitted well with the empirical data (X²/df = 60, CFI = 0.975, TLI = 0.969, RMSEA=0.078); and 3) Administrators' servant leadership has a significant positive direct effect on teachers' competencie (0.23), and also exerts a significant indirect effect through organizational support (0.263), the estimated value of the mediating effect for the path ASL→OS→TC is 0.064, with a 95% confidence interval (CI) of [0.026, 0.114] and a significance level of p < 0.001.